Charlie is my darling [videorecording (DVD)] : Ireland 1965 - Whitehead, Peter, 1937-2019-; Gochanour, Mick (ABKCO Music & Records, Inc., 2012)
Filmed in 1965 but never released, this is a behind-the-scenes look at the Rolling Stones' tour in Ireland just after "(I can't get no) Satisfaction" became a number one hit. Witness the band's first professionally filmed performances, the riots their appearances created, travel through the Irish countryside by train, time spent in motel rooms during impromptu songwriting sessions, and more.